Relationship between magnesium and lipids in patients with diabetes mellitus. Issue 2 (4th May 2019) - Jansen van Vuuren, JM; Pillay, S; Jansen van Vuuren, CJ
Abstract : Introduction: Non-communicable diseases, especially cardiovascular diseases (CVD), have become more prevalent across the world, more so in developing countries. Novel methods in the management of CVD risks in patients with diabetes mellitus, type 2 (DM2) requires constant attention and an ever-evolving approach. The role of magnesium supplementation in the management of CVD has been described, but the relationship between serum magnesium (Mg) and the lipid subsets have had conflicting results in different population groups. Methods: A cross-sectional study was performed by collecting data on patients with DM2 from a specialised diabetes clinic at Edendale Hospital, Pietermaritzburg, KwaZulu-Natal, South Africa, between July 1, 2015 and June 30, 2016. Lipid subsets (total cholesterol [TC], high-density lipoprotein cholesterol [HDL], low-density lipoprotein cholesterol [LDL] and triglycerides [TG]), age, sex and Mg were recorded for analysis. Results: A total of 495 clinical data sheets were analysed. The majority of participants were female (73.45%) with a mean age of 56.97 years. A statistically significant, positive, linear relationship was found between Mg and TC ( R = 0.11; p = 0.01) as well as Mg and LDL R = 0.14; p = 0.001), but not between Mg and HDL ( R = 0.02; p = 0.66) and Mg and TG ( R = 0.01; p = 0.82). Discussion: The results of this study are similar to findings by a group of researchers in China and differ when compared with studies observing Caucasian patients. It is plausible that intrinsic ethnic differences in lipid metabolism and the various ways in which magnesium requiring enzymatic processes are utilised may be responsible for the results found in the present study population versus those found in Caucasian study participants in other countries. More research is required to determine the effect of magnesium supplementation and CVD outcomes in the present study population.